2011
DOI: 10.3109/09638288.2011.611211
|View full text |Cite
|
Sign up to set email alerts
|

Service needs and service gaps among refugees with disabilities resettled in the United States

Abstract: Disabled refugees resettled in the U.S.A. have many unmet needs associated with gaps in-service delivery stemming from disconnections between refugee and disability service systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…In addition to the risk factors that may be present, ensuring refugees receive the mental health services they need can be challenging. Often, refugees face barriers such as stigma [20], low access to or quality of services [21], low cultural competence of practitioners [22], or a lack of knowledge about how services work and how they can be helpful [21]. Data on refugee engagement with mental health referrals varies, with studies reporting low referral acceptance (37%; [23]) and others reporting greater success (e.g., 74%; [6] and 50%; [24]).…”
Section: Risk Factors For Mental Health Symptoms and Barriers To Treamentioning
confidence: 99%
“…In addition to the risk factors that may be present, ensuring refugees receive the mental health services they need can be challenging. Often, refugees face barriers such as stigma [20], low access to or quality of services [21], low cultural competence of practitioners [22], or a lack of knowledge about how services work and how they can be helpful [21]. Data on refugee engagement with mental health referrals varies, with studies reporting low referral acceptance (37%; [23]) and others reporting greater success (e.g., 74%; [6] and 50%; [24]).…”
Section: Risk Factors For Mental Health Symptoms and Barriers To Treamentioning
confidence: 99%
“…The search for paid employment was further complicated by the language and educational qualifications required for a variety of jobs in host societies (Smith, 2012;Smith, Stephenson & Gibson-Satterthwaite, 2013;Werge-Olsen & Vik, 2012;Whiteford, 2005). Engaging in productive occupations was particularly challenging for refugees living with disabilities (Mirza, 2012;Mirza & Heinemann, 2012). Limited opportunities for employment and a lack of advocacy resources stigmatised these refugees and labelled them as 'non-employable', driving them further away from paid employment and prompting a reliance on social assistance (Mirza).…”
Section: Occupational Deprivationmentioning
confidence: 99%
“…Through targeted dialogues with stakeholders, we learned that existing refugee-and disability-focused employment programs were not meeting the needs of refugees with disabilities. For example, we found little to no evidence of efforts to make refugee-focused programs accessible through use of resources such as large print materials, sign language interpreters, and wheelchair-accessible locations [12]. We also found that few working-age refugees with disabilities had participated in disability-focused employment support services and programs available through the state Division of Rehabilitation Services [13]; in fact, most were unaware that work was a viable option for people with disabilities in the US.…”
Section: Engaging Community Partners Before Seeking Fundingmentioning
confidence: 81%
“…To help refugees find employment, US resettlement agencies also offer English-language training, as well as job search and job placement services during the first few months after resettlement [11]. Disability-related supports, such as wheelchair-accessible locations, sign language interpreters, or access to disability-related work incentives, are seldom accommodated within this support system [12]. Furthermore, service providers may perceive refugees with disabilities as unemployable and consequently channel them toward welfare assistance rather than encouraging them to pursue income-generating opportunities [9].…”
Section: Context Of Pridementioning
confidence: 99%
See 1 more Smart Citation